Pengaruh Kinerja Pegawai dan Kualitas Pelayanan Publik terhadap Kepuasan Masyarakt di Kantor Desa Banjar Tanggul Kecamatan Pungging Kabupaten Mojokerto - Muchamad Yusqi Al- Fantoriq; Rini Armin; Agoes Hadi Poernomo (Jurnal Visi Manajemen, 2025)
This study aims to analyze the influence of employee performance and public service quality on public satisfaction at the Banjar Tanggul Village Office, Pungging District, Mojokerto Regency. The background of this study is based on the understanding that village employees are the spearhead of public services, so good performance is a crucial factor in building public trust. In addition, professional public service quality is also a key component in creating public satisfaction. Good public service quality is a fundamental requirement for increasing citizens' trust in government institutions. The research method used is quantitative with an associative approach. The research sample consisted of 38 respondents determined using a purposive sampling technique. Data collection was carried out through questionnaires, then analyzed using multiple linear regression methods to test the effect of independent variables on the dependent variable. The results showed that employee performance has a positive and significant effect on public satisfaction. Similarly, the quality of public services has a significant positive effect on the level of public satisfaction. Simultaneously, these two variables have been proven to play an important role in increasing public satisfaction with village government services. The conclusion of this study is that the better the employee performance and the higher the quality of public services, the higher the public satisfaction. Therefore, village governments are advised to continuously improve their staff performance and service systems. Continuous improvement is key to achieving professional and satisfying public services. The implications of this research emphasize that employee professionalism, public service quality, and good village governance are crucial for building public satisfaction and trust.